Viral Susceptibility Range of the Fathead Minnow (Pimephales promelas) Poikilothermic Cell Line - Solis, Juan (1970)
The viral susceptibility range of a poikilothermic cell line derived from the fathead minnow (Pimephales promelas) (FHM) to infection by a number of homoiothermic viruses representing most of the presently recognized viral groups and a member of the psittacosis-lymphogranuloma-trachoma group of agents was studied. All infectious agents, except poliovirus types 1 and 3, infectious bursal agent, and an avian infectious bronchitis virus (IBV) strain, readily multiplied in the FHM cell culture system, producing a detectable cytopathic effect. Although inconclusive evidence was obtained with two other avian IBV strains, these results indicated the ability of the FHM cell culture system to readily support the propagation of a variety of cytopathogenic homoiothermic viral agents.